P53 PROTEIN EXPRESSION AND NUCLEAR-DNA CONTENT IN BREAST INTRADUCTAL PROLIFERATIONS - Schmitt, F. C.; Leal, C.; Lopes, C. (Wiley-Blackwell, 1995)
Immunohistochemical analysis of the p53 gene protein and cytometric assessment of nuclear DNA were performed in a series of 51 cases of intraductal breast proliferation. The series included 22 cases of intraductal hyperplasia without atypia, 6 cases of intraductal hyperplasia with atypia, and 23 cases of pure intraductal carcinoma. Expression of p53 protein was detected in one case of intraductal hyperplasia without atypia (4.5 per cent), one case of intraductal hyperplasia with atypia (16.6 per cent) and six cases of intraductal carcinoma (26.0 per cent). No significant correlation was observed between p53 expression and histological subtype of intraductal carcinoma. Aneuploidy was demonstrated in two cases of intraductal hyperplasia with atypia (33.3 per cent) and in 18 cases of intraductal carcinoma (78.2 per cent). All cases of intraductal hyperplasia without atypia were euploid. No significant association was observed between p53 protein expression and ploidy in intraductal hyperplasia. The only case of intraductal hyperplasia without atypia positive for p53 was euploid, whereas the only p53-positive case of intraductal hyperplasia with atypia was aneuploid. Among the intraductal carcinomas, only the aneuploid cases showed positivity for p53, regardless of histological subtype. The results suggest that some of the changes observed in invasive breast carcinoma, such as p53 expression and aneuploidy, are already present in breast intraductal proliferation, especially in areas with atypia and in intraductal carcinoma. The expression of p53 in breast intraductal proliferation may reflect the acquisition of p53 gene mutations in cells unable adequately to repair DNA damage, with genomic instability which would lead to clonal expansion and putative evolution to invasive disease.
Keywords: P53 EXPRESSION; DNA CONTENT; BREAST; INTRADUCTAL PROLIFERATION; BREAST CANCER